1999
DOI: 10.1046/j.1464-5491.1999.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors for Type 2 diabetes mellitus in a peri‐urban community in South Africa

Abstract: This previously unstudied community has an intermediate prevalence on the international scale of Type 2 DM, which is linked to potentially modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 30 publications
6
59
2
Order By: Relevance
“…The negative relationship between physical activity and diabetes was not observed in studies that used simple classification of subjects among inactive and active groups, 41,42 but has been reported in the few investigations that attempted a more precise evaluation of physical activity. 43 When addressing the dose -response issue in the relationship between physical activity and health-related outcomes, a review of existing evidence concluded that, despite the non-standardized measurements of physical activity in population studies and the need for further investigations, physical activity tended to relate to obesity, cardiovascular disease and diabetes in an inverse dose -response fashion. 44 -46 In both sexes of the urban and rural dwellers in the present study, there was a step-wise decrease in BMI, blood pressure and blood glucose levels across the increasing physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…The negative relationship between physical activity and diabetes was not observed in studies that used simple classification of subjects among inactive and active groups, 41,42 but has been reported in the few investigations that attempted a more precise evaluation of physical activity. 43 When addressing the dose -response issue in the relationship between physical activity and health-related outcomes, a review of existing evidence concluded that, despite the non-standardized measurements of physical activity in population studies and the need for further investigations, physical activity tended to relate to obesity, cardiovascular disease and diabetes in an inverse dose -response fashion. 44 -46 In both sexes of the urban and rural dwellers in the present study, there was a step-wise decrease in BMI, blood pressure and blood glucose levels across the increasing physical activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] The only data available to represent black Africans living in a rural area were collected in the former homeland of QwaQwa. 8 The study by Levitt et al 5 demonstrated a clear increase in the prevalence of diabetes associated with the length of stay in the urban area, and the 1998 South African Demographic and Health Survey (SADHS) 14 showed that the prevalence of overweight and obesity among black Africans was twice as high in the urban setting compared with the rural setting.…”
Section: Methodsmentioning
confidence: 99%
“…However, a number of epidemiological studies have been conducted in selected communities in the 1980s and 1990s. [5][6][7][8][9][10] These revealed a clear rural-urban gradient with higher prevalence in urban settings, in addition to a gradient across different population groups. Studies reported the highest prevalence in the Indian population, followed by the coloured and then the black population.…”
mentioning
confidence: 99%
“…Indeed in the community of mixed ancestral origin, the prevalence of diabetes is 10% [8], hypertension 18% [9] and low birthweight 14% [10]. Furthermore, an association between low birthweight and higher systolic and diastolic blood pressures (BP) and fasting blood glucose concentrations, but not measures of insulin sensitivity or secretion, has been reported in 20-year-old adults [11].…”
Section: Introductionmentioning
confidence: 99%